Development and Evaluation of Traditional Pinda Taila Loaded Gel Formulation - Sharma , Shruti; Chaudhary, Priyanka; Kumar, Ravinder; Thamman, Rakesh (International Research Journal of Ayurveda & Yoga, 2022)
The Indian system of Medicine; the Science of life, originated in the Vedic times of India, emphasizes on preventing the disease and maintaining the health. Sneha Kalpana, an Ayurvedic dosage form includes products of medicated taila and ghee, widely used internally as well as externally to treat various disorders. Pinda taila, herbal medicated oil intended for vatarakta (gout) and daha (burning sensation) in Ayurvedic system of medicine. It is applied topically in the form of Abhyanga. The name Pinda taila is because of pinda (semisolid) like appearance of final kalpna. The viscous appearance is marked by the presence of Sarja rasa and Madhucchishta. The dravyas present in the Pinda taila pacify the vitiated vatadosha and rakta. Vatarakta, a painful condition, is a disorder where vata is vitiated by rakta or vice-versa. The symptoms include ruk (pain), daha (burning sensation), toda (pricking pain) and shotha (inflammation) and managed with both internal and external chikitsas using gutika, niruha, lepa and sneha kalpna. In Ayurveda, Taila kalpana are included in Sneha Kalpana. In ancient literature there is immense description regarding manufacture of Sneha kalpana (ghrta and taila kalpanas) The Nomenclature of Sneha Kalpana is sum of two words Sneha and kalpana ; where Sneha means ‘fat’ and kalpana means ‘pharmaceutical process of medicaments’. 63 medicated tailas preparations are listed in official “Ayurvedic Formulary of India”. The present work aimed to develop a patient compliant gel preparation of Pinda taila as a substitute of oil for external application and its evaluation.